2007
DOI: 10.1089/clo.2006.0069
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Fertility of Cloned Male Cats Derived from Adult Somatic Cell Nuclear Transfer

Abstract: This study was designed to investigate the reproductive fertility by the natural breeding of cloned male cats with domestic female cats, and to measure endocrine hormone concentration related to male reproduction such as testosterone, leutinizing hormone (LH), and follicle stimulating hormone (FSH). Cloned A, B, C, and D cats produced three, two, four, and five kittens after natural mating with four domestic female cats, respectively, despite later puberty of the cloned D cat than those of the other cloned mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…In canids, SCNT has been applied not only to the cloning of companion dogs [12,13,16] but also to the preservation of endangered canine species [14,18]. In some species, cloned offspring produced by SCNT have been reported to show normal reproductive characteristics and successfully produce progeny by natural mating [1,2,6,7,21]. To our knowledge, however, there are no studies on the reproductive characteristics of cloned dogs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In canids, SCNT has been applied not only to the cloning of companion dogs [12,13,16] but also to the preservation of endangered canine species [14,18]. In some species, cloned offspring produced by SCNT have been reported to show normal reproductive characteristics and successfully produce progeny by natural mating [1,2,6,7,21]. To our knowledge, however, there are no studies on the reproductive characteristics of cloned dogs.…”
mentioning
confidence: 99%
“…, Hyun Ju OH 1) , Jung Eun PARK 1) , Jung Taek KANG 1) , Min Jung KIM 1) , Jung Hee YOON 2) , Jin Hwa CHANG 2) , Min Kyu KIM 3) , Goo JANG 1) and Byeong Chun LEE 1) Cloning technology using somatic cell nuclear transfer (SCNT) provides valuable opportunities for the fields of biomedical science, agriculture and preservation of endangered animals [2,6,17]. In canids, SCNT has been applied not only to the cloning of companion dogs [12,13,16] but also to the preservation of endangered canine species [14,18].…”
mentioning
confidence: 99%
“…We examined the reproductive ability of a male cloned dog and the behavioral traits of his offspring. Several previous studies reported that cloned animals had normal reproductive ability [ 3 5 18 ]. In this study, ten healthy puppies were produced by natural mating between a cloned male dog and a normal female dog in the DDTC.…”
Section: Discussionmentioning
confidence: 99%
“…Since successful cloning was first reported in cats (Shin et al 2002), the SCNT technology has been applied to African Wildcats (Gomez et al 2004), and has received much study. Indeed, feline SCNT has advanced to the point where second generation clones have been produced (Yin et al 2008b), and the fertility of cloned individuals by normal mating has been documented (Choi et al 2007). However, despite this progress, feline SCNT remains a relatively low-yield, labour and cost-intensive process.…”
Section: Esc: Future Directionsmentioning
confidence: 99%
“…Indeed, feline SCNT has advanced to the point where second generation clones have been produced (Yin et al. 2008b), and the fertility of cloned individuals by normal mating has been documented (Choi et al. 2007).…”
Section: Introductionmentioning
confidence: 99%